The Effect of Number Maze Media on the Beginning Arithmetic Ability of 5-6 Year Old Children at RA Perwanida 3 Palembang - Melani Firdha Maharani; Amir Hamzah; Tutut Handayani; Leny Marlina4 (Universitas PGRI Madiun, 2026)
Cognitive development describes how a child's mind functions and evolves, enabling the development of thinking skills. The use of maze-based learning media can alleviate boredom during the learning process due to its interactive nature and the engaging way the material is presented to children. The objective of this study was to determine the effect of